Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/cns.14033
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic and stress‐induced hyperglycemia in spontaneous intracerebral hemorrhage: A multicenter prospective cohort (CHEERY) study

Abstract: Introduction: Admission hyperglycemia is a common finding after spontaneous intracerebral hemorrhage (ICH) secondary to pre-existing diabetes mellitus (DM) or stress-induced hyperglycemia (SIH). Studies of the causal relationship between SIH and ICH outcomes are rare. Aim: We aimed to identify whether SIH or pre-existing DM was the cause of admission hyperglycemia associated with ICH outcomes. Methods: Admission glycosylated hemoglobin (HbA1c), glucose levels, and comorbidity data from the prospective, multice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…More importantly, we proved that SHR, as a continuous variable, was independently related to the 30-day and 1-year mortality in ICH patients with diabetes, but that was not the case for ABG. This result was similar to a recent study derived from the Chinese Cerebral Hemorrhage: Mechanisms and Intervention Study (CHEERY) [ 25 ]. In this study, Chen et al divided ICH patients into nondiabetic normoglycemia (NDN), diabetic normoglycemia (DN), diabetic hyperglycemia (DH), and stress-induced hyperglycemia (SIH) groups, and found that compared with patients with NDN, DH did not increase the risk of poor outcome and mortality, whereas SIH was an independent risk factor for pulmonary infection and 30- and 90-day death after ICH [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More importantly, we proved that SHR, as a continuous variable, was independently related to the 30-day and 1-year mortality in ICH patients with diabetes, but that was not the case for ABG. This result was similar to a recent study derived from the Chinese Cerebral Hemorrhage: Mechanisms and Intervention Study (CHEERY) [ 25 ]. In this study, Chen et al divided ICH patients into nondiabetic normoglycemia (NDN), diabetic normoglycemia (DN), diabetic hyperglycemia (DH), and stress-induced hyperglycemia (SIH) groups, and found that compared with patients with NDN, DH did not increase the risk of poor outcome and mortality, whereas SIH was an independent risk factor for pulmonary infection and 30- and 90-day death after ICH [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to a recent study derived from the Chinese Cerebral Hemorrhage: Mechanisms and Intervention Study (CHEERY) [ 25 ]. In this study, Chen et al divided ICH patients into nondiabetic normoglycemia (NDN), diabetic normoglycemia (DN), diabetic hyperglycemia (DH), and stress-induced hyperglycemia (SIH) groups, and found that compared with patients with NDN, DH did not increase the risk of poor outcome and mortality, whereas SIH was an independent risk factor for pulmonary infection and 30- and 90-day death after ICH [ 25 ]. Although Chen et al defined stress hyperglycemia by other method (having a diabetes history or HbA1c ≥ 6.5%, and admission blood glucose ≥ 7.8 mmol/L) [ 26 ] instead of SHR, the results from their study and ours indicated that stress hyperglycemia may be more closely associated with adverse prognosis in diabetic patients with ICH than admission hyperglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…[99][100][101] Stress hyperglycemia has also been reported to be associated with early hematoma enlargement and perihematomal edema aggravation in patients with ICH. 98,[101][102][103][104] Post-stroke stress hyperglycemia has been supposed to be associated with increased sympathetic activity and secretion of cortisol and norepinephrine, contributing to increased hepatic glucose output and insulin resistance. 105,106 Sykora et al demonstrated an association between stress hyperglycemia and decreased BRS in non-diabetic patients, which indicated that post-stroke hyperglycemia may be the result of autonomic shift toward sympathetic hyperactivity.…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Stress hyperglycemia secondary to acute stroke, usually assessed by stress hyperglycemia ratio, is characterized by transient hyperglycemia, and has been indicated to better predict mortality, poor neurological outcome, and infectious complications 99–101 . Stress hyperglycemia has also been reported to be associated with early hematoma enlargement and perihematomal edema aggravation in patients with ICH 98,101–104 …”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation